PATTERN OF ISLAMIC EDUCATION TEACHER INTERACTION WITH STUDENTS IN DEVELOPING PERSONALITY MUSLIM IN MEDIUM SCHOOL STATE VOCATIONAL SCHOOL 2 MEDAN - Asnil Aidah Ritonga; Indra Jaya; Muas Muas (Universitas Dharmawangsa Medan, 2020)
This study generally aims to determine: (1) students' practice of Islamic values at SMK Negeri 2 Medan, (2) Interaction of PAI teachers with students in developing Islamic values in students at SMK Negeri 2 Medan, and (3) Obstacles faced by PAI teachers in developing Islamic values in students at SMK Negeri 2 Medan. This study uses qualitative research methods, namely to understand the phenomenon of what is experienced by the research subject, for example behavior, perception, motivation, action and others, holistically and by way of description in the form of words and language, in a special natural context. and by utilizing various natural methods, and in reasonable field situations as they are without manipulation. Data was collected through observation, interviews, and documentation. The research findings show: (1) Students' practice of Islamic values at SMK Negeri 2 Medan consists of the following: (a) Religious morality includes; Faith, piety, have a strong faith, true to Islamic law, and have noble character; and (b) social care includes: Helping, Family, Caring, Tolerance, and Cooperation, (2) The pattern of teacher-student interaction in developing Islamic values in students using the basis of six methods, namely: the Exemplary Method; Habituation Method; Method of Giving Advice; Motivation Method; Persuasion Methods and; The Story Method, and (3) The obstacles faced by PAI teachers in developing Islamic values in students at SMK Negeri 2 Medan are: (a) Less optimal supervision of students outside school because teachers cannot supervise students in their activities. outside the school, because the teachers can only supervise in the school, while outside the school is the responsibility of the parents; (b) The backgrounds of students and parents are diverse, with religious knowledge that is not the same from one another; and (c) Unfavorable external environmental factors, Due to the association and swift challenges of the times and technology that cannot be dammed.